Can government funding revive zombie enterprises? Evidence from listed Chinese manufacturing enterprises - Yang, Yudi; Qi, Yong; Yang, Shuo (Journal of Business Economics and Management, 2021)
This study tests how different types of government funding affect the recovery of zombie enterprises in the manufacturing sector of China. The results show that funding for production and innovation can revive zombie enterprises in expanding industries, while funding for interest cannot. Furthermore, funding for production and innovation can share costs, increase investment in selling or innovation, and promote the scaling down of businesses through external governance effects, helping zombie enterprises to recover. Finally, none of the funding types can revive zombie enterprises in contracting industries; these can recover only through access to larger overseas markets.